Incidence and clinical impact of stroke complicating percutaneous coronary intervention - Werner, Nicolas; Bauer, Timm; Hochadel, Matthias; Zahn, Ralf; Weidinger, Franz; Marco, Jean; Hamm, Christian; Gitt, Anselm Kai; Zeymer, Uwe (Circulation. Cardiovascular interventions, 2013)
Background: Stroke is a rare but serious complication of percutaneous coronary interventions (PCIs). So far, scant information is available about the incidence and outcome of patients developing stroke after PCI for stable angina or acute coronary syndrome (ACS) in daily clinical practice in Europe today. - Methods and Results: Between 2005 and 2008, 46 888 patients undergoing PCI were enrolled into the PCI Registry of the Euro Heart Survey Programme (176 centers in 33 European countries) to document patient’s characteristics, PCI details, and hospital complications in different PCI indications. Stroke was observed in 0.4% of the procedures in the total population, in 0.3% of PCIs in elective patients, and in 0.6% in PCIs performed for ACS. The overall in-hospital mortality was 19.2% for patients who developed stroke (elective PCIs, 10.0%; PCI for ACS, 23.2%) compared with 1.3% for those without stroke (elective PCIs, 0.2%; PCI for ACS, 2.3%). In multivariate analysis hemodynamic instability, age ≥75 years, history of stroke, and congestive heart failure were found to be independent predictors for periprocedural stroke in ACS, whereas only PCI of a bypass graft and renal failure could be identified as independent predictors for stroke in elective patients. - Conclusions: Stroke as complication of PCI occurs rarely (0.4%) in clinical practice in Europe today. However, peri-interventional stroke is still associated with an exceedingly high in-hospital mortality rate. Most predictors for periprocedural stroke are not modifiable and cannot be diminished before PCI. Therefore, treatment of patients with stroke after PCI needs further research.